PHARMACOLOGICAL AND THERAPEUTIC PROFILE OF ANANTAMULA (HEMIDESMUS INDICUS (L.) R. BR.): A COMPREHENSIVE REVIEW (International Journal of Ayurveda and Pharma Research, 2017)
The vast field of Ayurvedic science is gaining more importance and popularity throughout the world because of its amazing therapeutic value. Since the beginning of human civilization, medicinal plants have been used by mankind for its therapeutic value. The World Health Organization estimated that 80% of people worldwide rely on herbal medicines for some aspect of their primary healthcare. Hemidesmus indicus is a widely used shrub in Indian folk medicine and considered as magical spiritual dream herb in Ayurvedic medication. It is used as a vital herb for healing many ailments and to treat diversified diseases. Following a large number of claims on the wide range of traditional medicinal properties of the plants, considerable effort have been made to verify its efficacy as a curative agent through pharmacological investigations. Different pharmacological experiments in vitro and in vivo models convincingly demonstrated the ability of Anantamula to exhibit analgesic, anti-inflammatory, antipyretic, antiarthritic, antioxidant, hepatoprotective, nephroprotective, antiepileptic, anticonvulsant, antileprotic, antiacne, antipsychotic, nootropic, antinociceptive, antidiarrhoeal, antigenotoxic, antiangiogenic, wound healing, antiulcer, larvicidal, antivenom, antithrombotic, antihyperlipaedaemic, antimicrobial and anticarcinogenic activities due to its remarkable biological activity and bioactive constituents. This plant is a good source of different bioactive chemical compound like Hemidesmin-1 and Hemidesmin-2, Î±-amyrin, Î²-amyrin, lupeol acetate, Î²-sitosterol, hemidesmol and hemidesterol which were responsible for many of the pharmacological activities. This review aims at providing an up-to-date overview of comprehensive account of the phytochemical investigation, therapeutic potential and pharmacological studies of Hemidesmus indicus.